2011
DOI: 10.4103/0019-5154.82480
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid : A new antioxidant in patients with pemphigus vulgaris

Abstract: Background:Increased reactive oxygen species (ROS) and lipid peroxidation are seen in many dermatologic disorders, for example, atopic dermatitis, psoriasis, vitiligo, acne vulgaris, pemphigus vulgaris (PV), lichen planus, and alopecia areata. ROS has an important role in the inflammation process. In PV, increased production of ROS leads to decline of antioxidants in plasma and red blood cells which results in oxidative stress. We aimed to evaluate the level of these antioxidants in PV patients and compare it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 25 publications
6
40
0
4
Order By: Relevance
“…For T1D is an important observation that this disease increases oxidative stress in tissues (Perez-Gutierrez & Damian-Guzman, 2012;Tan et al, 2007). Our results are in agreement with previous studies in which T1D increases plasma level of MDA, an important biological marker of lipid peroxidation (Bulum & Duvnjak, 2011;Yousefi et al, 2011). And it is suggested that the positive relationship between MDA and T1D is significant because disease leads to increased production of ROS and it may also involve lipid peroxidation (Országhová et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…For T1D is an important observation that this disease increases oxidative stress in tissues (Perez-Gutierrez & Damian-Guzman, 2012;Tan et al, 2007). Our results are in agreement with previous studies in which T1D increases plasma level of MDA, an important biological marker of lipid peroxidation (Bulum & Duvnjak, 2011;Yousefi et al, 2011). And it is suggested that the positive relationship between MDA and T1D is significant because disease leads to increased production of ROS and it may also involve lipid peroxidation (Országhová et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…skin and nervous system. This is shown in experimental models [11] and clinical association studies in several neurodegenerative disorders as Multiple Sclerosis [12], and skin diseases as pemphigus [13]. Animal models suggest additional protective effects in other organs, though clinical relevance remains unclear.…”
Section: Physiological Role Of Uric Acid In Humansmentioning
confidence: 98%
“…Low levels of selenium have been associated with about a 20-fold risk of opportunistic infections,7 increasing mycobacterium disease, poor quality of life,8 and a predictor of HIV associated mortality 7. In relation to skin diseases, selenium and other oxidant markers have been correlated with certain inflammatory skin diseases 911. Studies have also related pemphigus vulgaris to antioxidant status of patients,9 while low serum selenium and associated oxidative stress induction have been implicated in the pathogenesis of psoriasis 10,11.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to skin diseases, selenium and other oxidant markers have been correlated with certain inflammatory skin diseases 911. Studies have also related pemphigus vulgaris to antioxidant status of patients,9 while low serum selenium and associated oxidative stress induction have been implicated in the pathogenesis of psoriasis 10,11. Low selenium status has been associated with up to a 4-fold increased risk of developing skin cancers including malignant melanoma and epidermotropic cutaneous T cell lymphomas 12,13.…”
Section: Introductionmentioning
confidence: 99%